Pre- and post -exercise variation of blood parameters on performance endurance horses: a first race study from Algeria - Chikhaoui, M; Fadhéla, S; Belalia, CZA; Ayad, N (Journal of the Hellenic Veterinary Medical Society, 2023)
Abstract: This paper presents the first study conducted in Algeria to determine the pre and post-race hematological and biochemical parameters of horses of a 90 km endurance race for eliminated horses’ category and those who completed the races with good performance. This study was conducted on 15 endurance horses (10 Arabian Thoroughbred, 4 Arabian-Barb and 1 Barb). Nine (9) horses successfully completed the endurance race, whereas the other 6 were eliminated. Blood samples were collected from each animal before and after the end of the race. Whole blood samples were used for measuring the blood-biochemical parameters. Our results showed a significant increase in the hematological parameters (RBC, HB, Ht and MCV), the total leucocyte count, neutrophils and platelets for the group of horses who finished the race successfully. A significant decrease was noticed for the lymphocytes and eosinophils numbers while serum biochemical parameters showed a significant increase of Ca, TG, urea, U-A, AST and CK and a decrease of Mg, CHE, GLU and ƔGT. This study showed that, for the eliminated horses, there were significant changes in values of the total leucocytic count, lymphocytes, neutrophils, HB and Ht as compared to good performance horses. Serum biochemical parameters showed a significant increase of TG, U-A, AST and CK and a significant decrease of Ca, Mg, CHE and ƔGT. Most of the hemato-biochemical parameters of both the eliminated horses and those who completed the race successfully depicted significant differences. The results of this study suggested that biochemical findings could help identify horses with an increased risk of developing metabolic alterations before their elimination during competitive endurance races of different distances. Therefore, proper management protocols, standard feeding and watering with proper preparation of animals before the race could prevent electrolytes imbalance and pathological affections during racing.